Responses of pig embryos to amino acids - Rosenkrans, C.F.; Davis, Duane L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Mixtures of vitamins and amino acids produced detrimental effects on the development of pig embryos. However, addition of three amino acids, phenylalanine, methionine, and isoleuncine, enhanced pig embryo development.
Keywords: Swine; Embryo survival; Pregnancy; Amino acids